with a contribution by E. J. Luby, Excavations at Abu Salabikh, 1985-1986. Part I: Introduction and excavations on the Main Mound - Matthews, R. J.
Part II: Grave 185, by Edward J. Luby. Part III: Surface clearance: Main Mound, by R.J. Matthews.